2020
DOI: 10.21203/rs.3.rs-37898/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metabolic Healthy Obesity is associated with higher incidence of mild decrease estimate glomerular rate in rural Northeast Chinese

Abstract: Background Metabolic healthy obesity (MHO), as one phenotype of obesity, seems associate with lower risk of cardiovascular disease. However, MHO has close relationship with higher incidence of metabolic syndrome and diabetes. This study aims to investigate the prevalence of MHO at baseline, changes of obese metabolic phenotype at follow-up and its relationship with incidence of mildly reduced estimated glomerular filtration rate (eGFR) in rural Northeast Chinese. Methods The Chronic Kidney Disease Epidemiolo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…It is present in many chronic diseases, including diabetes, cardiovascular disease, hypertension, and CKD (6,7). Furthermore, several investigations revealed that being overweight and having metabolic syndrome (MS) was significantly linked to a moderate decline in eGFR (7)(8)(9)(10)(11)(12). Therefore, we hypothesized that there might be an association between IR or related surrogate markers and eGFR.…”
Section: Introductionmentioning
confidence: 99%
“…It is present in many chronic diseases, including diabetes, cardiovascular disease, hypertension, and CKD (6,7). Furthermore, several investigations revealed that being overweight and having metabolic syndrome (MS) was significantly linked to a moderate decline in eGFR (7)(8)(9)(10)(11)(12). Therefore, we hypothesized that there might be an association between IR or related surrogate markers and eGFR.…”
Section: Introductionmentioning
confidence: 99%